2017
DOI: 10.1016/j.jaci.2016.12.940
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Development of Allergy (MeDALL): Introducing novel concepts in allergy phenotypes

Abstract: Asthma, rhinitis, and eczema are complex diseases with multiple genetic and environmental factors interlinked through IgE-associated and non-IgE-associated mechanisms. Mechanisms of the Development of ALLergy (MeDALL; EU FP7-CP-IP; project no: 261357; 2010-2015) studied the complex links of allergic diseases at the clinical and mechanistic levels by linking epidemiologic, clinical, and mechanistic research, including in vivo and in vitro models. MeDALL integrated 14 European birth cohorts, including 44,010 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
173
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 183 publications
(193 citation statements)
references
References 131 publications
5
173
0
15
Order By: Relevance
“…The strong association between allergic multimorbidity and adult‐onset asthma observed in this study extends to adulthood observations well demonstrated in children. The association between asthma and allergic multimorbidity, including rhinitis, conjunctivitis, and dermatitis, is well described in children . Causal network analysis in school‐aged children has shown that allergen sensitization, allergic inflammation, environmental tobacco smoke exposure, pulmonary physiology, and rhinitis severity explained over half of the variance in asthma severity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong association between allergic multimorbidity and adult‐onset asthma observed in this study extends to adulthood observations well demonstrated in children. The association between asthma and allergic multimorbidity, including rhinitis, conjunctivitis, and dermatitis, is well described in children . Causal network analysis in school‐aged children has shown that allergen sensitization, allergic inflammation, environmental tobacco smoke exposure, pulmonary physiology, and rhinitis severity explained over half of the variance in asthma severity .…”
Section: Discussionmentioning
confidence: 99%
“…Asthma, a common noncommunicable disease, is a major public health issue, with over 300 million people affected worldwide . In children, several cohort studies showed that allergic diseases were associated with increased risk of asthma . A study of German children showed that asthma occurs in both sexes more frequently with coexisting allergies than as a single entity .…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have used multidimensional approaches to characterize the co‐evolution over childhood of a large set of respiratory/allergy symptoms; most studies have been limited to one dimension, either longitudinal latent class analysis dealing with a single symptom or cross‐sectional cluster analysis dealing with several outcomes . As new insights on multimorbidity are needed, studying co‐occurrence of allergic diseases is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Shared risk gene variants have been suggested in asthma, allergic rhinitis, and atopic eczema [21]. Monosensitization and polysensitization have been proposed as different phenotypes, especially the latter increasing the risk of multimorbidity [22, 23]. However, in a longitudinal cohort of children, the non-IgE conditions increased the risk of multimorbidity [3].…”
Section: Discussionmentioning
confidence: 99%